2019
DOI: 10.3389/fmicb.2019.01775
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variation in the Microbiome of Acropora Coral Species Does Not Reflect Seasonality

Abstract: The coral microbiome is known to fluctuate in response to environmental variation and has been suggested to vary seasonally. However, most studies to date, particularly studies on bacterial communities, have examined temporal variation over a time frame of less than 1 year, which is insufficient to establish if microbiome variations are indeed seasonal in nature. The present study focused on expanding our understanding of long-term variability in microbial community composition using two common coral species, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 89 publications
2
16
0
Order By: Relevance
“…21%) (electronic supplementary material, tableS4). These compositions are consistent with A. hyacinthus in Epstein et al[65] from the Great Barrier Reef. By contrast, FR A. hyacinthus collected in Mo'orea by Maher et al[66] in 2016 showed higher relative abundances of Endozoicomonas relative to our results, which may indicate shifts in microbial partners through time.…”
supporting
confidence: 87%
“…21%) (electronic supplementary material, tableS4). These compositions are consistent with A. hyacinthus in Epstein et al[65] from the Great Barrier Reef. By contrast, FR A. hyacinthus collected in Mo'orea by Maher et al[66] in 2016 showed higher relative abundances of Endozoicomonas relative to our results, which may indicate shifts in microbial partners through time.…”
supporting
confidence: 87%
“…Subsequently, GraftM results were manually curated by removing lineages identified as contamination. In brief, sample contamination is a combination of crosstalk from nearby wells and background contaminants (Minich et al, 2019), and we therefore followed an approach outlined previously (Epstein et al, 2019; Lee et al, 2015), which is based on the presumption that contaminant taxa are expected to have high relative abundances in negative controls but low relative abundances in samples. Therefore, lineages that exhibited a relative abundance of one or more orders of magnitude higher in the negative control compared to any sample were removed.…”
Section: Methodsmentioning
confidence: 99%
“…We conducted all diversity tests on the two coral species separately due to well-established differences in both alpha and beta diversity measures across host species ( Hernandez-Agreda et al, 2017 ; Epstein et al, 2019 ; Ziegler et al, 2019 ) that could have obscured significant differences between protocols. Three alpha diversity metrics were calculated to account for richness, evenness and phylogenetic diversity: observed species richness, Shannon diversity index and Faith’s Phylogenetic Diversity (PD) were calculated on rarefied data (1000 and 998 reads/sample for ASV and OTU data, respectively; these depths were chosen for each dataset to maintain comparability using the highest sample sizes without severely compromising rarefied alpha diversity).…”
Section: Methodsmentioning
confidence: 99%